2019
DOI: 10.1002/erv.2671
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and content of intrusive images in patients with eating disorders

Abstract: The aim of this study was to examine the characteristics and content of intrusive images in patients with different subtypes of eating disorders (EDs). Data were collected from 74 ED patients, 22 dieting, and 29 nondieting controls. Participants completed a set of self‐report questionnaires. Intrusive images of ED patients were significantly more repetitive, detailed, vivid, and distressing than intrusive images of dieting and/or nondieting controls. Most of the intrusive images were the same for the ED subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 44 publications
6
30
0
Order By: Relevance
“…However, the characteristics of these spontaneous mental images appear to be problematic. Spontaneous mental images related to eating, weight or shape were more vivid, negative and anxiety provoking, and involved more sensory modalities in individuals with eating disorder than in dieting and non-dieting controls (Kadriu et al, 2019;Somerville et al, 2007). Furthermore, spontaneous mental images of food were experienced as more distressing and were associated with a lower sense of control by individuals with binge eating behaviour than by healthy controls (Dugué et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, the characteristics of these spontaneous mental images appear to be problematic. Spontaneous mental images related to eating, weight or shape were more vivid, negative and anxiety provoking, and involved more sensory modalities in individuals with eating disorder than in dieting and non-dieting controls (Kadriu et al, 2019;Somerville et al, 2007). Furthermore, spontaneous mental images of food were experienced as more distressing and were associated with a lower sense of control by individuals with binge eating behaviour than by healthy controls (Dugué et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have shown that spontaneous mental imagery is also common in other mental disorders (Hackmann and Holmes, 2004), such as agoraphobia (Day et al, 2004), social phobia (Hackmann et al, 2000), hypochondria (Muse et al, 2010), obsessive compulsive disorder (Speckens et al, 2007), body dysmorphic disorder (Osman et al, 2004) and eating disorders (Hinrichsen et al, 2007;Kadriu et al, 2019;Somerville et al, 2007). These images are often related to negative early memories in content and meaning, which may be a transdiagnostic phenomenon (Hackmann and Holmes, 2004;Kadriu et al, 2019). However, several studies have shown that the content and nature of these images may also be disorder specific.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most commonly associated with social anxiety disorder, this phenomenon involves individuals experiencing conscious, invasive, recurrent mental imagery representing their fears (i.e. having an overweight body) (Kadriu et al 2019). One eating disordered patient describes the content of one such imagery experience, "In the image I see myself obese, with very fat thighs and a fat stomach."…”
Section: The Empiricist Model Of Anorexia Nervosamentioning
confidence: 99%